Research on relevance between k-core and clustering coefficient in complex network - Jun LIU; Jian-zhong QIAO (Tongxin xuebao)
K-core analysis is an effective way to simplify the graphic topological structure.Many researches considered that the higher value k is,the more important the core is in complex network.But the relevance analysis between k-core and clustering coefficient has not been made.Experimental results show that with the k-core analysis,the trend of the clustering coefficient is consistent with k.The proposed conclusions can provide theoretical basis and guidance for the future applications of k-core analysis in complex network.